Australian Higher Education: The Perfect Storm? - Locke, William (International Higher Education, 2021)
The heavy reliance of Australian universities on international student tuition has been exposed by the pandemic and, in particular, the federal government’s closure of international borders. This has prevented a significant number of students from entering the country to commence or continue their studies at Australian universities, leading to a reduction in income and precipitating a financial crisis. Some universities have adopted a longer-term, strategic response to this crisis, while others are struggling to survive.